Empirical Study Regarding the Effects of Minimum Quantity Lubricant Utilization on Performance Characteristics in the Drilling of Al 7075 - Kilickap, Erol; Huseyinoglu, Mesut; Ozel, Cihan (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2011)
Cutting fluids are difficult and expensive to recycle. These drawbacks mentioned can be reduced or eliminated by performing the cutting operations with minimum quantity lubrication or without using any cutting fluid. In this study, the effects of different cutting parameters on performance characteristics are studied empirically during the drilling of Al7075. The work piece surface roughness and the temperature changes due to the incurred heat at the cutting process are taken as performance outputs. In the experiments, HSS tools with a diameter of 8 mm and an angle of 118o were used. Minimum quantity lubrication (MQL), compressed air and dry processing (without the usage of any cooling liquid) techniques are used as the applied cooling technique. In the processing technique with MQL, the cooling liquid is sent pulverized on the interface between the work piece and the tool. Boron oil-water emulsion is used as the cutting liquid. As a result of the experiments, it is determined that better results are achieved with the MQL technique than with other cooling techniques. The best surface roughness is achieved at 20 m/min cutting speed and 0.1 mm/rev feed rate.
Keywords: MQL; aluminium composite; drilling; surface roughness